Polarclean as a Sustainable Reaction Medium for the Waste Minimized Synthesis of Heterocyclic Compounds - Ferlin, Francesco; Luciani, Lorenzo; Viteritti, Orlando; Brunori, Francesco; Piermatti, Oriana; Santoro, Stefano; Vaccaro, Luigi (Frontiers in Chemistry, 2019)
Herein we report the use of Polarclean as a novel polar aprotic solvent for the synthesis of decorated heterocycles via dipolar cycloaddition (isooxazoles) or intramolecular C‒H functionalization processes (benzo-fused chromenes). The use of Polarclean allowed to isolate the final products in good yields by simple solid filtration or liquid-liquid phase separation, avoiding the need for chromatographic purification. Moreover, since in the synthesis of benzo-fused chromenes, the metal catalyst is retained in the Polarclean, the catalyst/reaction medium can be easily reused for consecutive reaction runs, without any apparent loss in efficiency. This methodology is associated with a limited waste production. These results extend the applicability of Polarclean as a promising reaction medium for the replacement of toxic petrol-based solvent.